2002
DOI: 10.1007/s10052-002-0980-4
|View full text |Cite
|
Sign up to set email alerts
|

Masses and couplings of the lightest Higgs bosons in (M + 1)SSM

Abstract: We study the upper limits on the mass of the lightest and second lightest CP even Higgs bosons in the (M+1)SSM, the MSSM extended by a gauge singlet. The dominant two loop contributions to the effective potential are included, which reduce the Higgs masses by ∼ 10 GeV. Since the coupling R of the lightest Higgs scalar to gauge bosons can be small, we study in detail the relations between the masses and couplings of both lightest scalars. We present upper bounds on the mass of a 'strongly' coupled Higgs (R > 1/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
98
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 14 publications
2
98
0
1
Order By: Relevance
“…Second, a Higgs state with a sizeable singlet component can have a mass well below the lower LEP-bound of 114.7 GeV on a SM-like Higgs mass [6][7][8], without violating corresponding constraints [5] on its coupling to the Z boson. (Here we do not consider regions in parameter space where unconventional Higgs decays here could be possible.)…”
Section: Introductionmentioning
confidence: 99%
“…Second, a Higgs state with a sizeable singlet component can have a mass well below the lower LEP-bound of 114.7 GeV on a SM-like Higgs mass [6][7][8], without violating corresponding constraints [5] on its coupling to the Z boson. (Here we do not consider regions in parameter space where unconventional Higgs decays here could be possible.)…”
Section: Introductionmentioning
confidence: 99%
“…A possible cosmological domain wall problem [4] can be avoided by introducing suitable nonrenormalizable operators [5] that do not generate dangerously large singlet tadpole diagrams [6]. Hence, the phenomenology of the NMSSM deserves to be studied at least as fully and precisely as that of the MSSM.Radiative corrections to the Higgs masses have been computed [7,8,9,10] The extent to which there is a no-lose theorem for NMSSM Higgs discovery at the LHC has arisen as an important topic [13,17,18,19,20]. In particular, it has been found that the Higgs to Higgs pair decay modes can render inadequate the usual MSSM Higgs search modes that give rise to a no-lose theorem for MSSM Higgs discovery at the LHC.…”
mentioning
confidence: 99%
“…Radiative corrections to the Higgs masses have been computed [7,8,9,10] The extent to which there is a no-lose theorem for NMSSM Higgs discovery at the LHC has arisen as an important topic [13,17,18,19,20]. In particular, it has been found that the Higgs to Higgs pair decay modes can render inadequate the usual MSSM Higgs search modes that give rise to a no-lose theorem for MSSM Higgs discovery at the LHC.…”
mentioning
confidence: 99%
“…In this context, NMSSM has been discussed in the literature [14][15][16][17][18][19][20]. In the pre-discovery era, NMSSM was discussed mainly as a scenario allowing for a Higgs mass significantly above the values predicted by the MSSM [21][22][23][24][25]. The attention has been mostly focused on the new tree-level contribution to the Higgs mass coming from the singlet-doublet-doublet coupling in the superpotential, λSH u H d , which can be significant for low tan β values and O(1) values of λ.…”
Section: Introductionmentioning
confidence: 99%